Prediction of Long-Term Restenosis After Carotid Endarterectomy Using Quantitative Magnetic Resonance Angiography - Andereggen, Lukas; Amin-Hanjani, Sepideh; Beck, Jürgen; Luedi, Markus M.; Gralla, Jan; Schubert, Gerrit A.; Tortora, Angelo; Andres, Robert H.; Arnold, Marcel; Raabe, Andreas; Reinert, Michael (Frontiers in Neurology, 2022)
Background: To detect restenosis after carotid endarterectomy (CEA), long-term monitoring is required. However, nonselective follow-up is controversial and can be limited by costs and logistical considerations. Objective: To examine the value of immediate perioperative vessel flow measurements after CEA using quantitative magnetic resonance angiography (QMRA) to detect patients at risk of long-term restenosis. Methods: Prospective cohort study with long-term sonographic follow-up after CEA for symptomatic internal carotid artery stenosis (ICAs) >50%. In all patients, vessel flow was assessed both pre- and postoperatively by means of QMRA within +/- 3 days of surgery. Data on QMRA assessment was analyzed to identify patients at risk of restenosis for up to 10 years. Results: Restenosis was recorded in 4 of 24 patients (17%) at a median follow-up of 6.8±2.6 years. None of them experienced an ischemic event. Perioperative flow differences were significantly greater in patients without long-term restenosis, both for the ipsilateral ICA (p<0.001) and MCA (p=0.03), compared to those with restenosis (p=0.22 and p=0.3, respectively). The ICA mean flow ratio (p=0.05) tended to be more effective than the MCA ratio in predicting restenosis over the long term (p=0.35). Conclusion: Our preliminary findings suggest that increases in QMRA-based mean flow after CEA may be predictive of restenosis over the long term. Perioperative QMRA assessment could become an operator-independent screening tool to identify a subgroup of patients at risk for restenosis, in whom long-term monitoring is advised.